2020
DOI: 10.5194/esd-2020-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The synergistic impact of ENSO and IOD on the Indian Summer Monsoon Rainfall in observations and climate simulations - an information theory perspective

Abstract: Abstract. El-Niño southern oscillation (ENSO) and Indian Ocean Dipole (IOD) are two well-know temporal oscillations in the sea surface temperature (SST), which both are thought to influence the interannual variability of the Indian Summer Monsoon Rainfall (ISMR). Until now, there has been no measure to assess the simultaneous information exchange (IE) from both ENSO and IOD to ISMR. This study explores the information exchange from two source variables (ENSO and IOD) to one target (ISMR). First, in order to il… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Under the influence of La Niña, which always modulates precipitation of oceanic origin that is the most important source of precipitation in the tropical north and south Atlantic Ocean, an increase in precipitation is usually observed. 52 Likewise, there is a significant relationship between the ENSO and precipitation in Asia; 53 particularly, the ENSO contributes to Indian monsoon interannual variability, 18,54 bringing about an increase in the precipitation over the Indian Peninsula during La Niña events. In this region, the influence of recycling supports the importance of precipitation from terrestrial origin.…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of La Niña, which always modulates precipitation of oceanic origin that is the most important source of precipitation in the tropical north and south Atlantic Ocean, an increase in precipitation is usually observed. 52 Likewise, there is a significant relationship between the ENSO and precipitation in Asia; 53 particularly, the ENSO contributes to Indian monsoon interannual variability, 18,54 bringing about an increase in the precipitation over the Indian Peninsula during La Niña events. In this region, the influence of recycling supports the importance of precipitation from terrestrial origin.…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be attributed to the emergence of simulation biases inherited from the driving EC-EARTH GCM, e.g., cold surface & sea surface temperatures over the Mediterranean compared to ERA-20C forcing. A study by Pothapakula et al (2020) showed that the biases in the driving GCMs emerged into the regional climate simulations resulting in unrealistic process chains. Downscaling the EC-EARTH3 (latest version of EC-EARTH) which has smaller bias in the surface air temperatures, SST (Döscher et al, 2021) might assist in further understanding the state and process chains linking the North-West Mediterranean Sea and the Vb-cyclone precipitation in historical & future periods.…”
Section: Discussionmentioning
confidence: 99%
“…Vb-cyclone precipitation Methods from information theory were recently used in quantifying interactions among sub-systems, especially in climate (Pothapakula et al, 2019(Pothapakula et al, , 2020 Title Suppressed Due to Excessive Length 9 Krug et al, 2021b;Ruddell et al, 2019). Transfer entropy (TE) was especially used in detecting and quantifying the direction of information exchange between two or more sub-systems.…”
Section: Quantifying Process Chain Between North-western Mediterranean Sea Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate teleconnections such as the El Nino-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) which are related to SST changes are frequently used to make reliable seasonal forecasts [10]. And both ENSO and IOD are synergistic predictors in the monsoon core region [11]. Sea surface temperature climatology is a crucial prerequisite for ocean modelling.…”
Section: Introductionmentioning
confidence: 99%